Optimalisasi Sanitasi dan Kebersihan Lingkungan dalam Mewujudkan Desa Sehat dan Sejahtera: Studi Kasus Desa Saringembat melalui Pendekatan Kolaboratif dan Edukasi Masyarakat - Zesa Dinda Auliya; Maharani Ikaningtyas (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
This study discusses the optimization of sanitation and environmental cleanliness in realizing a Healthy and Prosperous Village in Saringembat Village through a collaborative approach and community education. This program is based on the SDGs point of Healthy and Prosperous Villages, with a focus on the importance of clean environmental conditions and good sanitation as the foundation for public health. The methods used include surveys of locations for illegal waste disposal, interviews, and focus group discussions (FGD) with the Head of the Village Consultation Agency (BPD) and local waste bank managers. The survey results show five main waste disposal points that became the primary focus of the program. Collaboration with village officials resulted in full support in the form of drafting a village regulation on cleanliness and the installation of CCTV to prevent illegal waste disposal. The program also involved community service activities starting from Sawir Hamlet, Krajan Hamlet, and Demaan Hamlet, with active community participation and direct coordination from the hamlet heads. The implementation of the program proved to increase residents' awareness of the importance of sanitation, reduce the risk of infectious diseases, and create a healthier environment. The role of students as activity initiators was appreciated for their ability to revive the gotong royong (mutual cooperation) culture, which had been abandoned.